Spring ritual baking in Russian calendar rites of the middle Volga region - Chernysheva, Yu.S. (Perm Federal Research Centre Journal, 2023)
The article discusses the peculiarities of ritual baking in the Middle Volga region. The names and symbolic meaning of ritual baking, its place of the calendar cycle, ceremonial and ritual actions performed with bakes are considered. The purpose of this study is to determine the functions of ritual baking in the calendar ritual of the Volga region Russians. The work was carried out on the materials of folklore and ethnographic expeditions of the Institute of Humanitarian Studies of the Ural Branch of the Russian Academy of Sciences in 2004, 2018–2023, expeditions of the Department of Oral Folk Art of Lomonosov Moscow State University in the 1980s. The study showed that the calendar timing of the baking crosses tradition changes throughout the XX century – from the Feast of the Holy Cross to Epiphany. This is due to the consonance of the names, the same symbolism of the holidays and the «falling out» of the Sredokrestie from the national calendar in Soviet times. Ladder baking retains their calendar timing for the Ascension holiday, but by the middle of the XX century they practically cease to exist, as the church holiday got replaced by alternative secular ones – the feast of the first furrow, etc. The tradition of baking «larks» has only survived to the present and is actively in existence, but its original meaning has changed. Christian and agrarian symbolism has been replaced by the motifs of the seasonal change.